2017
DOI: 10.1111/os.12324
|View full text |Cite
|
Sign up to set email alerts
|

Internal Fixation of Complicated Acetabular Fractures Directed by Preoperative Surgery with 3D Printing Models

Abstract: The purpose of this article is to evaluate the efficacy and feasibility of preoperative surgery with 3D printing-assisted internal fixation of complicated acetabular fractures. A retrospective case review was performed for the above surgical procedure. A 23-year-old man was confirmed by radiological examination to have fractures of multiple ribs, with hemopneumothorax and communicated fractures of the left acetabulum. According to the Letounel and Judet classification, T-shaped fracture involving posterior wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…Koshimune [28] compared conventional open lumbopelvic fixation with minimally invasive procedure for unstable Preoperative planning is always essential for complicated injuries, especially pelvic and acetabular fractures. Recently, it has been shown that the preoperative planning of complicated fractures can be improved more effectively with 3D printing technology [13,14] . In view of our experience about this group of cases, we summarize advantages with 3D printing model as follow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koshimune [28] compared conventional open lumbopelvic fixation with minimally invasive procedure for unstable Preoperative planning is always essential for complicated injuries, especially pelvic and acetabular fractures. Recently, it has been shown that the preoperative planning of complicated fractures can be improved more effectively with 3D printing technology [13,14] . In view of our experience about this group of cases, we summarize advantages with 3D printing model as follow.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies show that the surgical treatment of acetabular or pelvic fracture was completed more effectively by surgeons who took advantage of 3D printing technology [13][14] . In addition to patientspecific 3D printing external template [15] , there is no doubt that the biggest advantage lies in the use of equal proportion printing model for simulated operation, which can confirm the ideal sequence of fracture reduction and fixation or the osteotomy site, and determine the optimal position of the implants.…”
Section: Introductionmentioning
confidence: 99%
“…3D printing technology has brought new hope for achieving precise drilling of Kirschner wires. The application of 3D printing technology in orthopaedic surgery is developing rapidly and has been successfully used in many medical fields, such as for clearer 3D demonstration of disease and operation plans for doctor–patient communication; for preparation of a large amount of customized casts and insoles; manufacture of guides that are highly matched with the anatomy of the patient, which facilitates the positioning of implants and reduces the operation time; and printing of customized metal implants to improve operative outcomes. To prepare the customized guides, we need to first collect the CT data of the patient to conduct the 3D image reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) printing technologies have attracted increasing interest in medicine, with various applications in the orthopaedic field. 3D printing is applied in many areas in orthopaedics, ranging from production of customized surgical tools and prostheses, implants and internal fixations to operative rehearsal and visualization of complex surgical procedures [5][6] . To tackle the problems mentioned with the DAPSQ reconstruction plate, we have used personalized 3D printed DAPSQ plates to fix complex acetabular fractures since 2014 [7][8] .…”
Section: Introductionmentioning
confidence: 99%